Social action with children and families : a community development approach to child and family welfare - Cannan, Crescy, 1947-; Warren, Chris, 1946- (State of welfare., 1997)
"Meeting the needs of children at the same time as promoting family life is more than a question of resources: it needs a cultural change in social services - a rediscovery and a modernisation of the social action and community development traditions in social work. In Social Action with Children and Families the authors argue that ways must be found to work together to promote environments in which children can flourish, and to develop forms of public life which are friendly to children and their parents." "The central aim of Social Action with Children and Families is to help those working in this field to find a new, more positive sense of direction and purpose. It will be invaluable reading to those studying social work, social policy and public administration as well as to all professionals working in these areas."--Jacket